Developing Scientific Writing Skills Instrument Using An Inquiry-Based Approach to Local Wisdom Dilemma Stories for Senior High School Students - Riansi, Erwin Salpa; Yuliarti, Yuliarti; Sultoni, Achmad; Sohnui, Suhailee (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to develop a valid and reliable instrument for assessing scientific writing skills using an inquiry-based approach to local wisdom dilemma stories. A Design and Development method, based on the Ellis & Levy model, was adopted. The method consisted of six steps: (a) issues; (b) goal setting; (c) model design and development; (d) model testing; (e) model evaluation of the test findings; and (f) application model. Two hundred seventy-three high school students from three Indonesian schools were recruited as the pilot sample. Purposive sampling was used to select the participants. Five experts evaluated the instrument's validity. The Aiken formula for content validity proof yielded a respectable score of 0.86. According to the measurement model reliability evaluation, the instrument is in the dependable category, which comprises Composite Reliability with a value of 0.89. Confirmatory factor analysis revealed the Root Mean Square Error of Approximation value to be 0.043 < 0.08 and the Goodness of Fit Index to be 0.98 > 0, 90 or the declared model by the data obtained in the field and can be used in a wide range of measurements. The findings of this study have important implications for educational assessment and instructional design. Developing a valid and reliable instrument to measure scientific writing skills through an inquiry-based approach using local wisdom dilemma stories provides educators with a culturally relevant and pedagogically sound tool. This instrument can support more accurate evaluations of students' writing competencies and foster critical thinking and contextual understanding in scientific writing instruction at the high school level.